2015
DOI: 10.1007/s00421-015-3274-x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle variables of importance for physiological performance in competitive football

Abstract: The findings emphasize the complexity of parameters predicting physical football performance with Yo-Yo IR1 and HAD as the best predictors of total distance, while high expression of Na(+)-K(+) ATPase proteins and the Yo-Yo IR2 test are better predictors of high-intensity performance. Finally, sprint performance relates to skeletal muscle fiber-type composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 40 publications
2
53
2
Order By: Relevance
“…For the computation of YYIR1 test global means, SDs and quantiles (Figure 2), 239 studies or subgroups with a total of 4,726 participants (median of reported age means = 21.1, inter quartile range [IQR] of reported age means = 17.8–24.5 years) were used (Krustrup and Bangsbo, 2001; Krustrup et al, 2003; Mohr et al, 2003, 2010, 2016; Weston et al, 2004; Castagna et al, 2005, 2006b, 2008; Atkins, 2006; Thomas et al, 2006; Rampinini et al, 2007, 2008, 2010; Mujika et al, 2009; Ben Abdelkrim et al, 2010; Chaouachi et al, 2010; Dupont et al, 2010; Veale et al, 2010; Wong et al, 2010; Buchheit et al, 2011; Chtourou et al, 2011; Chuman et al, 2011; Cobley et al, 2011; Markovic and Mikulic, 2011; Matthys et al, 2011; Roberts et al, 2011; Spencer et al, 2011; Ueda et al, 2011; Alemdaroglu et al, 2012; Boullosa et al, 2012, 2013a,b; Cihan et al, 2012; Cone et al, 2012; Deprez et al, 2012, 2014, 2015a,b; Heaney, 2012; Ingebrigtsen et al, 2012, 2014; Lim, 2012; Scanlan et al, 2012, 2014; Shalfawi et al, 2012, 2013; Teplan et al, 2012a,b, 2013; Vernillo et al, 2012; Berdejo-del-Fresno and González-Ravé, 2013; Cullen et al, 2013; Faude et al, 2013; Higham et al, 2013; Idrizovic and Raickovic, 2013; Manzi et al, 2013; Oliveira et al, 2013; Román-Quintana et al, 2013; Wylie et al, 2013; Yuki et al, 2013; Casamichana et al, 2014, 2015; Clarke et al, 2014; Fabregat-Andres et al, 2014; Fanchini et al, 2014, 2015a,b; Hammouda et al, 2014; Hermassi et al, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the computation of YYIR1 test global means, SDs and quantiles (Figure 2), 239 studies or subgroups with a total of 4,726 participants (median of reported age means = 21.1, inter quartile range [IQR] of reported age means = 17.8–24.5 years) were used (Krustrup and Bangsbo, 2001; Krustrup et al, 2003; Mohr et al, 2003, 2010, 2016; Weston et al, 2004; Castagna et al, 2005, 2006b, 2008; Atkins, 2006; Thomas et al, 2006; Rampinini et al, 2007, 2008, 2010; Mujika et al, 2009; Ben Abdelkrim et al, 2010; Chaouachi et al, 2010; Dupont et al, 2010; Veale et al, 2010; Wong et al, 2010; Buchheit et al, 2011; Chtourou et al, 2011; Chuman et al, 2011; Cobley et al, 2011; Markovic and Mikulic, 2011; Matthys et al, 2011; Roberts et al, 2011; Spencer et al, 2011; Ueda et al, 2011; Alemdaroglu et al, 2012; Boullosa et al, 2012, 2013a,b; Cihan et al, 2012; Cone et al, 2012; Deprez et al, 2012, 2014, 2015a,b; Heaney, 2012; Ingebrigtsen et al, 2012, 2014; Lim, 2012; Scanlan et al, 2012, 2014; Shalfawi et al, 2012, 2013; Teplan et al, 2012a,b, 2013; Vernillo et al, 2012; Berdejo-del-Fresno and González-Ravé, 2013; Cullen et al, 2013; Faude et al, 2013; Higham et al, 2013; Idrizovic and Raickovic, 2013; Manzi et al, 2013; Oliveira et al, 2013; Román-Quintana et al, 2013; Wylie et al, 2013; Yuki et al, 2013; Casamichana et al, 2014, 2015; Clarke et al, 2014; Fabregat-Andres et al, 2014; Fanchini et al, 2014, 2015a,b; Hammouda et al, 2014; Hermassi et al, …”
Section: Resultsmentioning
confidence: 99%
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…The performance improvements in these studies were accompanied by elevated expression of muscle proteins, which were suggested to be important factors in counteracting fatigue development during intense intermittent exercise (Iaia and Bangsbo, 2010). In addition, these muscle variables were demonstrated to correlate to high intensity running distance in a soccer game (Mohr et al, 2016). Thus, a very high and constant exercise intensity during speed endurance production training and concomitant long recovery intervals may be speculated to be a stimuli for a wide range of adaptations in muscular systems that are important for improving fatigue resistance during intense intermittent exercise.…”
Section: Discussionmentioning
confidence: 99%
“…8,31 In support of these putative mechanisms, content of HADHA and Na + , K + -ATPase subunits has been shown to be important determinants of running capacity and high-intensity performance, respectively, in football players. 21 In addition, given no changes were observed in sprint and agility performance in 10-20-30, it is unlikely the enhancement in Yo-Yo IR1 performance was related to an increased ability to accelerate or perform highspeed turns. This is further supported by the improved sprint performance observed in SIT without concomitant increases in Yo-Yo IR1 performance.…”
Section: Discussionmentioning
confidence: 97%
“…20 In addition, muscle content of Na + , K + -ATPase subunits and maximal activity of oxidative enzyme 3-hydroxyacyl-CoA-dehydrogenase (HADHA) were shown to predict the capacity to perform high-intensity runs in football players. 21 Sprint training, consisting of 6-10-second duration sprints, on the other hand, improves acceleration and sprint ability in trained football players, 9 which are associated with higher anaerobic enzyme activity and abundance of muscle ion transport proteins involved in Ca 2+ and H + handling. 10,22 Repeated short (~5 seconds) sprints with short recovery periods (~10 seconds) may enhance intense intermittent running performance during a Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1), despite a decrease in muscle content of proteins involved in oxidative metabolism in well-trained football players, 5 implying that further investigations are required to understand skeletal muscle adaptations underpinning training-induced improvements in football-specific performance.…”
Section: Introductionmentioning
confidence: 99%